141k views
5 votes
5(bx-2ab)=b(x-7a)+5ab solving for x

2 Answers

2 votes

Answer:

x = 2a

Explanation:

5(bx-2ab)=b(x-7a)+5ab

5bx - 10ab = bx - 7ab + 5ab

4bx = 8ab

x = 8ab/(4b)

x = 2a

User Alexander Gorban
by
5.5k points
3 votes

Answer:

x = 2a

Explanation:

5(bx-2ab)=b(x-7a)+5ab

Distribute

5bx - 10ab = bx -7ab +5ab

Combine like terms

5bx - 10ab = bx -2ab

Add 10 ab to each side

5bx - 10ab+10ab = bx -2ab+10ab

5bx = bx+8ab

Subtract bx from each side

5bx - bx = bx -bx +8ab

4bx = 8ab

Divide each side by 4b

4bx/4b = 8ab/4b

x = 2a

User Abu Yousuf
by
5.8k points